Combined theoretical and experimental studies on Myristica fragrans fruit rind extracts as an efficient protecting agent for mild steel corrosion in 1M HCl - Asha Thomas; A.T. Jeejarani; Athira Ajayan; Abraham Joseph (Next Sustainability)
The corrosion inhibition property of Nutmeg (Myristica fragrans) fruit rind extract against mild steel corrosion in 1M HCl at 303 K, 308 K, and 313 K is discussed in this paper. The aqueous extract (MFW), rich in ascorbic acid, is characterized using UV–visible spectroscopy, while GC-MS analysis of the ethanolic extract (MFE) identifies seven organic compounds, including ascorbic acid. Electrochemical Impedance Spectroscopy (EIS) reveals a capacitive behavior, with maximum inhibition efficiencies of 97 % at a 3 % concentration of MFE and 92 % at a 4 % concentration of MFW at ambient temperature. Tafel polarization studies confirm the mixed-type inhibition mechanism. Adsorption and kinetic studies support physisorption as the dominant mode of interaction. MFE demonstrates superior inhibition efficiency, particularly concerning exposure time and temperature, due to the synergistic adsorption of these organic molecules onto the metal surface. Theoretical calculations and molecular simulations substantiate the protective efficiency of the inhibitor molecules through adsorption on the metal surface. From the analysis, it is concluded that the abundantly available fruit rind extract of Myristica fragrance is a very efficient inhibitor against mild steel corrosion in HCl medium.